Cardiac complications and diabetes in thalassaemia major: a large historical multicentre study. (20th September 2013) - Pepe, Alessia; Meloni, Antonella; Rossi, Giuseppe; Caruso, Vincenzo; Cuccia, Liana; Spasiano, Anna; Gerardi, Calogera; Zuccarelli, Angelo; D'Ascola, Domenico G.; Grimaldi, Salvatore; Santodirocco, Michele; Campisi, Saveria; et al.
Summary: The relationship between diabetes mellitus (DM) and cardiac complications has never been systematically studied in thalassaemia major (TM). We evaluated a large retrospective historical cohort of TM to determine whether DM is associated with a higher risk of heart complications. We compared 86 TM patients affected by DM with 709 TM patients without DM consecutively included in the Myocardial Iron Overload in Thalassaemia database where clinical/instrumental data are recorded from birth to the first cardiovascular magnetic resonance (CMR) exam. All of the cardiac events considered were developed after the DM diagnosis. In DM patients versus non‐DM patients we found a significantly higher frequency of cardiac complications (46·5% vs. 16·9%, P  < 0·0001), heart failure (HF) (30·2% vs. 11·7%, P  < 0·0001), hyperkinetic arrhythmias (18·6% vs. 5·5%, P  < 0·0001) and myocardial fibrosis assessed by late gadolinium enhancement (29·9% vs. 18·4%, P  = 0·008). TM patients with DM had a significantly higher risk of cardiac complications [odds ratio (OR) 2·84, P  < 0·0001], HF (OR 2·32, P  = 0·003), hyperkinetic arrhythmias (OR 2·21, P  = 0·023) and myocardial fibrosis (OR 1·91, P  = 0·021), also adjusting for the absence of myocardial iron overload assessed by T2* CMR and for the covariates (age and/or endocrine co‐morbidity). In conclusion, DM significantly increases the risk for cardiac complications, HF, hyperkinetic arrhythmias and myocardial fibrosis in TM patients.